Repression over responsibility: sanctioning of environmental activism - Emiline Smith; Angus Nurse (Environmental Research Letters)
Conservation offers evidence-based insights into the state of ecosystems and biodiversity, while activism amplifies conservation goals through public and political engagement. Despite the importance of this relationship, a troubling pattern has emerged: environmental activism is increasingly met with disproportionate criminalization and punitive responses by many governments worldwide. Such repression not only threatens individual activists but also undermines the broader conservation movement by discouraging public participation and stifling dissent, ultimately jeopardizing our collective ability to address the planet’s most pressing challenges. This short perspective examines the growing trend of targeting environmental activists and discusses the potential consequences this may have for conservationists and anyone else concerned about the profound, immediate threats of climate change and environmental exploitation.